Social and economic effects of petroleum development in non-OPEC developing countries : synthesis report - McLin, Jon (ILO GenevaCH, 1986)
Examines the present and potential effects of oil and gas production on the economic and social development of Third World non-OPEC petroleum producers. Emphasis is placed on the petroleum sector's contribution to employment generation, industry, and manpower development.